2021
DOI: 10.1097/oi9.0000000000000165
|View full text |Cite
|
Sign up to set email alerts
|

Hip fracture care during the COVID-19 pandemic: retrospective cohort and literature review

Abstract: Objectives: The goal of this study was to investigate whether the COVID-19 pandemic has affected hip fracture care at a Level I Trauma hospital. The secondary goal was to summarize the published hip fracture reports during the pandemic. Design: A retrospective cohort study. Setting: Level I Trauma Center. Patients/Participants: Eighty-six operatively treated hip fracture patients age ≥65 years, occurring from Janua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…Length of hospital stay was reported to be similar during the pandemic period in a retrospective study on senior citizens for hip fractures due to a fall [40]. Likewise, the LOS in the hospital, and hospitalization/mortality rates in the ED were similar in the pandemic (25.8%) and pre-pandemic periods (22.8%) in the present study whereas mortality rates in ED at both periods were quite low.…”
Section: Discussionsupporting
confidence: 67%
“…Length of hospital stay was reported to be similar during the pandemic period in a retrospective study on senior citizens for hip fractures due to a fall [40]. Likewise, the LOS in the hospital, and hospitalization/mortality rates in the ED were similar in the pandemic (25.8%) and pre-pandemic periods (22.8%) in the present study whereas mortality rates in ED at both periods were quite low.…”
Section: Discussionsupporting
confidence: 67%
“…To our knowledge, this is the first study to evaluate standards of care and outcomes for hip fracture patients throughout the entire COVID-19 pandemic. This work builds on an earlier study conducted by Topor et al, 13 which examined 30-day mortality in 86 patients with surgically treated hip fractures stratified by three time periods during the ongoing pandemic. The authors found no difference in time to surgery or 30-day mortality, but, in contradiction to this study, no difference in length of stay.…”
Section: Discussionmentioning
confidence: 97%
“…The authors found no difference in time to surgery or 30-day mortality, but, in contradiction to this study, no difference in length of stay. However, the duration of Tobor et al 13 was limited to a small portion of the COVID-19 pandemic, a study period that would be contained within the early pandemic group of our analysis. As such, this study offers valuable insight into the effects on hip fracture patient care over the entire COVID-19 pandemic not presently available in the literature.…”
Section: Discussionmentioning
confidence: 99%